2022
DOI: 10.4314/tjpr.v20i6.27
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of ulinastatin on postoperative complications and cognitive function in elderly patients with esophageal cancer after thoracic laparoscopic surgery

Abstract: Purpose: To investigate the therapeutic effect of ulinastatin on postoperative complications and cognitive function in elderly patients with esophageal cancer after thoracic laparoscopic surgery. Methods: A total of 100 elderly in-patients with esophageal cancer who had undergone thoracic laparoscopic surgery from April 2019 to December 2020 were selected and randomly assigned to control and study groups. Patients in control group received conventional treatment, while those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…CF = (NC/ICN)100 ………………. (2) where CF is the Clone formation rate, and ICN is the inoculated cell number…”
Section: Clone Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…CF = (NC/ICN)100 ………………. (2) where CF is the Clone formation rate, and ICN is the inoculated cell number…”
Section: Clone Formationmentioning
confidence: 99%
“…Esophageal carcinoma (EC) is a common malignant tumor of the digestive tract. Statistics have revealed that more than 300,000 people die from EC every year globally [1,2] and its 5-year survival rate was reported to range from 10 -40 % [3,4]. Esophageal squamous cell carcinoma (ESCC) is the main pathological type of EC [5].…”
Section: Introductionmentioning
confidence: 99%